Dear Liv - Börekçi, Naz A.G.Z. (FormAkademisk, 2023)
…for me you are a bright, wise, and compassionate woman and an exemplary academic, providing an embracing environment for her colleagues. I was most fortunate to be introduced to you first in 2018 for the preparations of the Learn X Design 2019 Ankara conference. That initial shy communication conducted via emails, turned into regular online meetings when I joined the DRS EdSIG convening group in late 2019, and then into intense engagements as we started working collectively for the Learn X Design 2021 Jinan conference. Many were involved with their hard work and valuable contribution, but your involvement in particular, has been a motivation for me in the process. We spent many productive hours in online meetings, organizing the event, and building the background to realise it. I love the tapestry that you have behind you on screen in the background, and I love that it is you who have made it. I love you telling us that you will go skiing after the meeting. I can actually imagine you in your suit, grasping your gear, and starting to ski immediately as you step out of the cabin. That is how skilled and talented I find you. Many times, I have felt a reciprocal understanding between the two of us, which has always been reassuring and encouraging. I have learned a lot from you. Thank you for being a friend!